2012
DOI: 10.3934/mbe.2012.9.601
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the effects of introducing a new antibiotic in a hospital setting: A case study

Abstract: The increase in antibiotic resistance continues to pose a public health risk as very few new antibiotics are being produced, and bacteria resistant to currently prescribed antibiotics is growing. Within a typical hospital setting, one may find patients colonized with bacteria resistant to a single antibiotic, or, of a more emergent threat, patients may be colonized with bacteria resistant to multiple antibiotics. Precautions have been implemented to try to prevent the growth and spread of antimicrobial resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Recent theoretical studies support these claims: Wu et al have shown that maintaining variation in stockpiled influenza drugs might substantially reduce resistance [ 21 ], while Joyner et al demonstrated the benefits of developing new antibiotics and expanding the range of possible antimicrobial treatments [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical studies support these claims: Wu et al have shown that maintaining variation in stockpiled influenza drugs might substantially reduce resistance [ 21 ], while Joyner et al demonstrated the benefits of developing new antibiotics and expanding the range of possible antimicrobial treatments [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…We reviewed only models where AB consumption was introduced as an independent parameter, because we consider the process of developing resistance as a function of time and antibiotic consumption. That is why some papers were excluded at the stage of full text analysis (Bergstrom et al, 2004 ; Miller et al, 2004 ; Boni and Feldman, 2005 ; Huovinen, 2005 ; Mera, 2005 ; Reluga, 2005 ; Webb et al, 2005 ; Levin and Rozen, 2006 ; Schinazi, 2006 ; D'Agata et al, 2007 ; Zalounina et al, 2007 ; Drovandi and Pettitt, 2008 ; Pienaar et al, 2009 ; Artalejo et al, 2010 ; Haber et al, 2010 ; Kardas-Sloma et al, 2011 ; Kouyos et al, 2011 ; Opatowski et al, 2011 ; Wang et al, 2011 ; Banks et al, 2012 ; Chamchod and Ruan, 2012a , b ; Deng et al, 2012 ; Hurford et al, 2012 ; Joyner et al, 2012 ; Sotto and Lavigne, 2012 ; Yahdi et al, 2012 ; Horsburgh et al, 2013 ; Lee et al, 2013a , b ; Worby et al, 2013 ). The seven remaining models were classified according to the type of link between resistance and AB consumption.…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacometrics has in this context arisen as a formidable tool to bridge and link between key concepts in these disciplines and to provide a rationale, scientific framework throughout the drug development continuum as well as in clinical applications [1,2]. There are case studies which suggest that basing optimization of treatment on pharmacometric assessments improves the risk-management of MDR pathogens in the clinical realm by minimizing the failures and mistakes associated with inappropriate or careless use of antibiotic therapies [3,4]. …”
mentioning
confidence: 99%